Вплив індуктивності мережі на режими та характеристики тиристорного компенсатору реактивної потужності - Чиженко, О.І.; Трач, І.В. (Технічна електродинаміка, 2017)
Досліджено вплив технологічних змін індуктивного опору xa електричної мережі на характеристики та параметри тиристорного мостового компенсатора реактивної потужності, який встановлено з метою підтримання належних значень cosφ. З’ясовано, що при збільшенні цього опору максимальне значення реактивної потужності, що може генерувати у мережу тиристорний компенсатор (ТРК), теж збільшується, але при цьому глибина регулювання реактивної потужності зменшується. Для покращення якості вхідного струму ТРК, тобто зменшення його коефіцієнта гармонік до значень менших 5%, пропонується в процесі регулювання під навантаженням змінювати індуктивність реактора, який увімкнено між конденсаторною батареєю і тиристорним мостом. Ці зміни відбуваються стрибкоподібно шляхом перемикання за допомогою симисторів відпайок обмоток цих реакторів. При налаштуванні вхідного LC контуру ТРК на чотирикратну частоту з’являється можливість приєднання індуктивно-тиристорного регулятора безпосередньо до вершин трикутника встановленої в мережі конденсаторної батареї без втручання в її обладнання. Завдяки цьому з’являється можливість плавного регулювання реактивної потужності, яка генерується у мережу конденсаторною батареєю. Прослеживается влияние технологических изменений индуктивного сопротивления электрической сети на характеристики и параметры тиристорного мостового компенсатора реактивной мощности, установленного в ней с целью поддержания надлежащих значений cosφ. Установлено, что с увеличением этого сопротивления максимальное значение реактивной мощности, генерируемой в сеть тиристорным регулируемым компенсатором (ТРК), тоже увеличивается, но при этом сужается глубина регулирования реактивной мощности. Для улучшения качества входного тока ТРК, т.е. уменьшения его коэффициента гармоник до значений меньших 5%, предлагается в процессе регулирования под нагрузкой осуществлять уменьшение индуктивности реактора, включенного между конденсаторной батареей и тиристорным мостом. Эти изменения осуществляются скачкообразно путем переключения с помощью симисторов отпаек обмоток этих реакторов. При настройке входного контура ТРК на четырехкратную частоту появляется возможность подключения индуктивно-тиристорной части регулятора непосредственно к установленным в сети конденсаторным батареям без какого-либо вмешательства в их оборудование. Благодаря этому возникает возможность плавного регулирования реактивной мощности действующей в сети конденсаторной установки фиксированной мощности. An impact of technology changes of inductive resistance of electrical network can be observed on the characteristics and parameters of the bridge thyristor compensator of reactive power established in it to maintain proper values of cosφ. It is determined that with the increase of this resistance, a maximum value of reactive power generated into the network by thyristor compensator of reactive power, also increases, whereas a depth of reactive power control narrows. Thus, when increasing inductive resistance of the network by 25%, the depth of reactive power control, calculated value of which is xa for the constant parameter, will be reduced almost by half. To improve the quality of input current of thyristor compensator of reactive power (aka line current), i.e. to reduce its harmonic distortion to the values lower than 5%, it is proposed to decrease the reactor inductance, which is connected between capacitor bank and thyristor bridge, during the process of on-load changing. These changes are carried out step-wise by switching the taps of reactors’ windings using additional thyristors. Thus, when the depth of reactive power control is 50% and the input LC circuit of thyristor compensator of reactive power is tuned to quadruple frequency (with respect to the mains power frequency), the number of taps that is needed is two. When inductive resistance of the network increases, the frequency of LC circuit setup decreases, which leads to the reduction of taps until their complete absence. When tuning the input circuit of thyristor compensator of reactive power to quadruple frequency, it is possible to connect inductive-thyristor part of the controller directly to the capacitor banks installed in the network without any interference into their equipment. This results in a smooth control of reactive power in the network of capacitor unit with a fixed power.